Kendala Peran Pemerintah Kota Gunungsitoli dalam Meningkatkan Kesiapsiagaan Masyarakat terhadap Resiko Bencana Gempa Bumi - Septin, Septin; Alhadi, Zikri (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research aims to identify the factors that become obstacles in the implementation of the role of the Gunungsitoli City Government in improving community preparedness for earthquake disaster risk. This research is a qualitative study that applies the descriptive method. The research findings indicate that there are two obstacles that hinder the role of Gunungsitoli City in improving community preparedness for earthquake disaster risk, namely internal and external obstacles.